A guide to behavioural experiments in bipolar disorder. (3rd January 2020) - Palmier‐Claus, Jasper; Wright, Kim; Mansell, Warren; Bowe, Samantha; Lobban, Fiona; Tyler, Elizabeth; Lodge, Christopher; Jones, Steve
Abstract: Behavioural experiments are an important component of cognitive–behavioural therapy. However, there exists little up‐to‐date guidance on how to conduct these in people with a diagnosis of bipolar disorder. This paper provides recommendations on how to conduct behavioural experiments in this population. The aim is to upskill and empower clinicians to conduct behavioural experiments. The paper combines the expertise of senior clinicians working in the United Kingdom. The article starts by providing general advice on conducting behavioural experiments in people with bipolar disorder. It then offers specific examples of behavioural experiments targeting cognitions around the uncontrollability and danger of affective states, and related behavioural strategies, which have been implicated in the maintenance of bipolar mood swings. The article finishes by providing examples of behavioural experiments for non‐mood related difficulties that commonly occur with bipolar experiences including perfectionistic thinking, need for approval, and intrusive memories. Behavioural experiments offer a useful therapeutic technique for instigating cognitive and behavioural change in bipolar disorder. Conducted sensitively and collaboratively, in line with people's recovery‐focused goals, behavioural experiments can be used to overcome mood‐ and non‐mood related difficulties.